2007
DOI: 10.1007/s10550-007-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Family life in the digital home — domestic telecommunications at the end of the 20th century

Abstract: This paper describes results from the first stage of a long-term study of people's use of ICT (information and communications technology) products and services in the domestic environment. It is part of BT's ongoing commitment to understanding, modelling and meeting the needs of its residential customers. At one level the research has already generated significant knowledge that has led directly to commercial benefit; at a second it has validated a number of research methods needed to capture the data to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Authors have described activities, materials and interactions with artifacts involved in the practices of, amongst others, gardening [36], pottering [78,93], religious practice [90,92], health monitoring [1,39], interpersonal communication [3,4,26], domestic networks management [38], and resource consumption [74]. Works in this genre often rely on an ongoing relationship between participants and researchers as a way to gain an insider's understanding of the more intimate aspects of domestic practices.…”
Section: Ongoing Domestic Practicesmentioning
confidence: 99%
“…Authors have described activities, materials and interactions with artifacts involved in the practices of, amongst others, gardening [36], pottering [78,93], religious practice [90,92], health monitoring [1,39], interpersonal communication [3,4,26], domestic networks management [38], and resource consumption [74]. Works in this genre often rely on an ongoing relationship between participants and researchers as a way to gain an insider's understanding of the more intimate aspects of domestic practices.…”
Section: Ongoing Domestic Practicesmentioning
confidence: 99%
“…The results indicate that the most important variables when considering the adoption factors are, gender, race, education, and income. Previous studies that examined the adoption of ICTs such as the computer [25,27], the telephone [3], internet [2] and broadband [1] in the households and its subsequent impact on users have included these variables. Since home computers, the telephone, and the internet are grouped within the same technology cluster [21], the socioeconomic variables that have been employed to study one technology can also be used to study the others.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Other studies reinforce this sentiment of maintaining rhythm, but express it quite differently. Anderson et al (1999) demonstrate how families can have an affinity with domestic rhythms in other homes. This remote awareness is used to avoid intrusion by deliberately avoiding calls at inconvenient times, such as meal times or when the caller knows the recipient will be watching a particular television programme.…”
mentioning
confidence: 91%
“…These were analysed to detect common threads of usage and thus adoption behaviour that persisted across the different communication devices. The technologies selected were: the traditional telephone (Anderson et al,1999;Kline 2003); emerging technologies such as domestic networking (Grinter and Edwards, 2005) and Instant Messaging (IM) (Diane et al, 2002;Grinter and Palen, 2002); and finally novel prototype technologies such as interactive message and video communication devices providing asynchronous text and pictorial images between family groups (Hutchinson et al, 2003) and 'media spaces' (Hindus et al, 2001) The first identified theme that consistently cut across all the identified technologies was the need for any given technology to fit in with natural domestic rhythms. Work patterns, schooling, preparing and eating meals and relationships with neighbours are examples of important rhythms that mould domestic routine.…”
mentioning
confidence: 99%
See 1 more Smart Citation